Pemanfaatan Media Sosial dalam Manajemen Hubungan Masyarakat sebagai Upaya Meningkatkan Partisipasi Masyarakat di Era Pandemi - Dian Agustini (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Public relations management serves as an informer as well as an intermediary between educational institutions and the community that can be done with publication activities. Even in the era of the COVID-19 pandemic, public relations managers must be able to publish appropriately and use appropriate media as well. This research aims to find out the use of social media as a public relations management publication media to increase public participation in the development of educational institutions in the pandemic era. The method used in the preparation of this article is a qualitative descriptive research method, which is a research method that uses qualitative data and is described descriptively, data obtained from the literature study of various sources and analyzed with qualitative data analysis. The results showed that social media is one of the appropriate publication media used by public relations management to increase public participation in the era of the COVID-19 pandemic, where various activities carried out are directly restricted by the government.